2007
DOI: 10.1038/sj.emboj.7601778
|View full text |Cite
|
Sign up to set email alerts
|

PtdIns(4,5)P-restricted plasma membrane localization of FAN is involved in TNF-induced actin reorganization

Abstract: The WD-repeat protein factor associated with nSMase activity (FAN) is a member of the family of TNF receptor adaptor proteins that are coupled to specific signaling cascades. However, the precise functional involvement of FAN in specific cellular TNF responses remain unclear. Here, we report the involvement of FAN in TNF-induced actin reorganization and filopodia formation mediated by activation of Cdc42. The pleckstrin-homology (PH) domain of FAN specifically binds to phosphatidylinositol-4,5-bisphosphate (Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 78 publications
(104 reference statements)
3
43
0
Order By: Relevance
“…Although the connection between p75 and RhoA is well understood (see above), it remains to be discovered how other TNFRs link to small GTPases. As discussed above, death-domain-binding adaptors are not necessarily required to mediate Cdc42 activation and cytoskeletal changes (Puls et al, 1999), and molecules such as FAN that transmit signals from the TNFR to the cytoskeleton and bind to other parts of the intracellular domain of the TNFR are now being identified (Haubert et al, 2007) (Fig. 4).…”
Section: A Morphogenetic Signalling Pathway?mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the connection between p75 and RhoA is well understood (see above), it remains to be discovered how other TNFRs link to small GTPases. As discussed above, death-domain-binding adaptors are not necessarily required to mediate Cdc42 activation and cytoskeletal changes (Puls et al, 1999), and molecules such as FAN that transmit signals from the TNFR to the cytoskeleton and bind to other parts of the intracellular domain of the TNFR are now being identified (Haubert et al, 2007) (Fig. 4).…”
Section: A Morphogenetic Signalling Pathway?mentioning
confidence: 99%
“…Furthermore, certain TNFα-dependent effects on the cytoskeleton do not require the receptor's death domain (Peppelenbosch et al, 1999), but instead require a more membraneproximal region of the receptor, the neutral sphingomyelinase (NSMase)-activating domain (Adam-Klages et al, 1996). One adaptor protein, factor associated with N-SMase activity (FAN), which binds to this region, is required for TNFα-dependent activation of Cdc42 and filopodium formation (Haubert et al, 2007). Other molecules that have been implicated in TNFα-stimulated modulation of GTPases include MAP kinases, phosphoinositide 3-kinases, PLCγ1 and ceramide (Hanna et al, 2001;Kutsuna et al, 2004;Papakonstanti and Stournaras, 2004).…”
Section: Tnfα Modulates the Cytoskeleton Via Rho-family Gtpasesmentioning
confidence: 99%
See 1 more Smart Citation
“…54 PH domains are generally involved in interaction with phosphoinositides or mediate protein-protein interactions. The PH-like domain of the small human BEACH protein factor associated with neural sphingomyelinase (FAN) is shown to bind PI(4,5)P2, 55 but it is not known whether the PH-like domain of ALFY is functional. The PH-like and WD40 domains show a moderate degree of conservation throughout human BEACH proteins whereas the BEACH domain is highly conserved.…”
Section: Adaptor Proteinsmentioning
confidence: 99%
“…Involvement of PA Binding to the PH Domain in the Localization of RA-RhoGAP at Plasma Membrane-It has been reported that PH domain-containing proteins localize at the membrane by binding of the PH domains to phospholipids (35,43). Therefore, we examined whether binding of the PH domain of RA-RhoGAP to PA was responsible for membrane localization.…”
Section: Volume 286 • Number 8 • February 25 2011mentioning
confidence: 99%